1994
DOI: 10.1093/oxfordjournals.jae.a036802
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Contested Markets and the Degree of Tradedness of Agricultural Commodities: an Empirical Test in Zaire

Abstract: The theory of contestable markets is used to derive predictions of the extent to which agricultural commodities behave as traded or nontraded goods. These predictions are confirmed with Zairian data which show that there is wide variation in the response of domestic commodity prices to real exchange rate changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Results for the goodness-of-fit (R 2 ) show that this model explains 95 percent of monthly domestic price variation for rice over the 1983 to 1998 period in both well-connected and isolated markets. This alone suggests that rice is probably a tradable (Kyle and Swinnen 1994), as common sense would also suggest. World rice prices have a positive influence on Tanzanian rice prices, as would be expected.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Results for the goodness-of-fit (R 2 ) show that this model explains 95 percent of monthly domestic price variation for rice over the 1983 to 1998 period in both well-connected and isolated markets. This alone suggests that rice is probably a tradable (Kyle and Swinnen 1994), as common sense would also suggest. World rice prices have a positive influence on Tanzanian rice prices, as would be expected.…”
Section: Resultsmentioning
confidence: 89%
“…However, it is rare that macroeconomic analyses allow for the fact that major food staples, such as maize, might behave as non-tradables (Delgado 1992). It is rarer still that analysts test the tradability assumption for food staples (Kyle and Swinnen 1994).…”
Section: Differences Between Tradable and Non-tradable Agricultural Gmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as Nigeria is concern, in respect of high food prices, the country has experienced worst food crisis and price hike in the recent time. Kyle and Swinnen (1994) concluded that high food prices have caused day to day changes in consumption pattern of consumers especially of commodities such as rice, yam, wheat etc. These changes in consumer consumption patterns affect the savings of consumers and uncertainty prices, both of food and non-food items generate enthusiasm among people towards earning more and more.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on analyzing factors associated with consumer choice [1,2]. According to Engel, proportion of expenditure spent on food is inversely related to total income [3,4].…”
Section: Introductionmentioning
confidence: 99%